Investment in Cryptocurrencies: lessons for asset pricing and portfolio theory. Issue 10 (25th February 2022) - Dempsey, Michael; Pham, Huy; Ramiah, Vikash
ABSTRACT: We consider the performance of cryptocurrencies in the light of fundamental asset pricing and portfolio theory. We observe how a traditional focus on reducing asset return volatility with Markowitz diversification misses the significance of such volatility for growth. The recognition that asset growth is more likely subject to exponential or continuously compounding growth characteristics reveals that asset volatility can be exploited both across assets and across investment periods to deliver superior returns.